Young massive star cluster formation in the Galactic Centre is driven by global gravitational collapse of high-mass molecular clouds - Barnes, Ashley T.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. Young massive clusters (YMCs) are the most compact, high-mass stellar systems still forming at the present day. The precursor clouds to such systems
Gesehen am 31.05.2019